Physico-Chemical Properties and Bacteriological Analysis of Mangrove Water from Mangrove Forest of Gbaramatu Kingdom Delta, Nigeria - Abdulganiyu Galadima Mohammed; Angela Chika Udebuani; Reuben Nwoye Okechi (BIORE Scientia Publisher, 2025)
Mangrove water is habitat for aquatic organisms and is important for water supply, transportation, agricultural and industrial activities. This study aims at evaluating the physico-chemical properties of mangrove water from the mangrove forest of Gbaramatu Kingdom Warri South West LGA, Delta State, Nigeria. The physical and chemical properties of the mangrove water sample were determined using standard methods of AOAC, APHA, and ASTM. Enumeration of total heterotrophic bacteria in the mangrove water sample was evaluated by colony‐forming units (CFU) method. Bacterial isolates were identified and characterized by colony and morphology characteristics, microscopic examinations and biochemical tests. The mangrove water demonstrated 33 °C, 8.3, 35.63 NTU, 23915.53 µS/cm, 2213.13 mg/L, 10411.99 mg/L, 38.40 mg/L, 18545.11 mg/L, 5.40 mg/L, 18.51 mg/L, and 52.00 mg/L mean value of temperature, pH, turbidity, conductivity, salinity, TH, TSS, TDS, DO, BOD, and COD, respectively. The concentration of total alkalinity, bicarbonate, chloride, sulphates, phosphate, and nitrate in the mangrove water were 142.15 mg/L, 110.05 mg/L, 349.97 mg/L, 78.05 mg/L, 1.50 mg/L, and 0.07 mg/L, respectively. The mangrove water sample contains high significant number of heterotrophic bacteria. The values of physical and chemical parameters in the mangrove water sample are above the recommended values by WHO for domestic use.